2019
DOI: 10.1111/cpr.12669
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from miR‐375‐overexpressing human adipose mesenchymal stem cells promote bone regeneration

Abstract: Objectives:The present study aimed to investigate whether exosomes derived from miR-375-overexpressing human adipose mesenchymal stem cells (hASCs) could enhance bone regeneration. Materials and Methods:Exosomes enriched with miR-375 (Exo [miR-375]) were generated from hASCs stably overexpressing miR-375 after lentiviral transfection and identified with transmission electron microscopy, nanosight and western blotting.The construction efficiency of Exo (miR-375) was evaluated with qRT-PCR and incubated with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
240
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(241 citation statements)
references
References 50 publications
1
240
0
Order By: Relevance
“…miR-92-a-3p in MSC-derived exosomes may increase chondrogenesis and suppress cartilage degeneration via wnt5A, thus, can serve as treatment for OA [ 70 ]. Moreover, ADSC-derived exosomes carrying miR-375 target 3′UTR of insulin like growth factor binding protein 3 in bone marrow-derived stem cells in vitro to promote bone formation which may serve as a good therapeutic option for calvarial defects [ 71 ]. However, in-depth investigation is required to apply these therapies in in-vivo models and humans.…”
Section: Disease Treatment Using Mirna-enriched Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-92-a-3p in MSC-derived exosomes may increase chondrogenesis and suppress cartilage degeneration via wnt5A, thus, can serve as treatment for OA [ 70 ]. Moreover, ADSC-derived exosomes carrying miR-375 target 3′UTR of insulin like growth factor binding protein 3 in bone marrow-derived stem cells in vitro to promote bone formation which may serve as a good therapeutic option for calvarial defects [ 71 ]. However, in-depth investigation is required to apply these therapies in in-vivo models and humans.…”
Section: Disease Treatment Using Mirna-enriched Evsmentioning
confidence: 99%
“…Although GMP ensures obtaining clinical-grade EVs, which can be loaded with RNAs, the problem of ultra-purification for human interventional studies still persist. Moreover, batch-to-batch variation pose an obstacle for human studies [ 71 ]. Future studies are required to develop appropriate protocols for miRNA-enriched EVs.…”
Section: Clinical Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Other research showed that exosomes from miR-92a-3p-overexpressing MSCs promoted chondrogenesis in vitro and suppressed cartilage degradation in an OA mouse model by repressing WNT5A expression [157]. Recent studies showed that exosomes from miR-375-overexpressing MSCs promoted osteogenic differentiation in vitro by inhibiting the expression of insulin-like growth factor binding protein 3 and improved bone regeneration in a calvarial defect rat model [158].…”
Section: Gene Overexpression To Improve the Function Of Msc-derived Ementioning
confidence: 99%
“…Released exosomes are internalized in target cells and subsequently affect their biological behaviors and promote the tissue regenerative process [ 18 , 19 , 20 ]. Exosomes secreted from mesenchymal stem cells (MSCs) can promote the proliferation, migration, and tube formation of endothelial cells in vitro, angiogenesis in vivo [ 21 , 22 , 23 , 24 ], and in vivo bone regeneration [ 25 , 26 , 27 ]. The microRNAs (miRNAs) in exosomes play the role of promoting endothelial cell proliferation and vessel formation, and regulating the osteogenic differentiation of targeted MSCs into mature osteoblasts and the subsequent mineralization process [ 18 , 28 ].…”
Section: Introductionmentioning
confidence: 99%